Analyzing the challenges faced by recently qualified nurses in radiation therapy nursing at Japan's National University Hospitals: Uncovering the determinants of difficulty - Tsuchihashi, Yumiko; Matsunari, Yuko (Asia-Pacific journal of oncology nursing, 2024)
Newly graduated nurses embarking on careers in radiation therapy nursing at Japan's National University Hospitals face a spectrum of challenges, many of which have received limited attention in existing literature. This study aimed to uncover the primary difficulties encountered by these nurses, with a specific focus on their implications for training and systematic education. Employing a survey involving nurses from five prestigious medical institutions in Japan, we explored the real-time experiences and challenges within radiation therapy nursing. Our investigation concentrated on adverse events and the requisite knowledge for effective symptom management. The results illuminated a notable divergence in experiences among nurses, with particular challenges emerging in the treatment of head and neck cancers, especially when combined with chemotherapy. The data emphasized the pivotal role of certified nurses in offering support and knowledge transfer in complex cases, underscoring the importance of peer support and consultations. The findings underscored a significant variance in experiences among nurses, with specific difficulties encountered in the management of head and neck cancers, particularly in conjunction with chemotherapy. The data highlighted the essential role of certified nurses in providing support and knowledge dissemination in challenging scenarios, underscoring the significance of peer support and consultations. This study provides an overview of the landscape, highlighting the critical role of peer consultation and the need for advancements in the educational framework for radiation therapy nurses.